Fitness clubs activities in Kharkіv - Стадник, Світлана (Slobozhanskyi Herald of Science and Sport, 2018)
Svitlana Stadnyk Purpose: to analyze the fitness clubs activities in Kharkiv. Material & Methods: analysis of literary sources; analysis of documents; survey (questionnaire) methods of mathematical statistics. The study was conducted on the basis of 12 fitness clubs in Kharkiv among their clients. Results: the study identified the main differences and competitive advantages of fitness clubs in Kharkiv; the preferences of club customers for choosing a fitness club, popular fitness programs, additional services, as well as effective sources of information about the club and the main reasons for leaving the fitness club. Conclusions: found that the market of fitness services in Kharkov is characterized by 297 fitness establishments and the main leaders in the local market are network fitness clubs. The ways of increasing the effectiveness of fitness clubs in Kharkiv are determined.